Методика трехмерного математического моделирования процесса формообразования гнутых профилей замкнутого сечения - Забара, Александр Сергеевич (НТУ "ХПИ", 2014)
В статье разработана методика трехмерного математического моделирования гнутых профилей замкнутого сечения методом осадки трубной заготовки, обеспечивающая получение качественных профилей. Модель методом конечных элементов позволяет рассчитать геометрию формоизменения трубной заготовки по всем проходам, определить параметры напряженно-деформированного состояния трубы в любой точке и в любой момент времени.

In the article the technique of three-dimensional mathematical modeling of cold-formed sections closed section by rainfall billets, provides high-quality profiles. Using the software Ansys Ls-dyna, allows you to simulate a continuous process of formation in three calibers, to determine a more accurate geometry for the cross-sectional profile of the finished, and also allows for a more accurate analysis of the reliability of the results. For better visibility and credibility of the results, as well as to obtain more precise geometry for the cross-sectional profile of the finished, simulated a continuous process of forming GPZS. Analysis of the results of calculations using the developed mathematical model showed the actual shape of the deformation zone, the final forming of cold-formed sections closed section at the front end, and in the steady process - power parameters. Model finite element method allows to calculate the geometry of the forming tube blank on all passes, to determine the parameters of the stress-strain state of the pipe at any point and at any time.
Method three-dimensional mathematical modeling process formoobrazovanyya hnutыh closed cross-section profiles
Keywords: калибровка; конечно-элементная модель; осадка трубы; трубные заготовки; bent profile; closed section; forming; power parameters